On the development of an experimental rig for hydrogen micromix combustion testing - Giannouloudis, Alexandros; Sun, Xiaoxiao; Corsar, Michael; Booden, Scott J.; Singh, Gaurav; Abbott, David; Nalianda, Devaiah; Sethi, Vishal (The Combustion Institute, 2021)
This work describes the development of a combustion rig, aimed at testing hydrogen-fuelled micromix burners for aero gas-turbines at pressures up to 15barg, inlet-air temperatures up to 600K and equivalence ratios (Φ) from leanblow- out to 0.5. It discusses the test facility used, and the design procedure of the experimental apparatus: the requirements of it, the design choices and implementation of instrumentation. Emphasis is placed on the design and manufacture of the burner. Comparison between Additive Manufacturing (AM) and micro-machining techniques for the sub-millimetre injection points shows that further research is needed in this area, to achieve adequate geometric accuracy of the injection holes economically. This rig forms a unique facility for hydrogen micromix testing, offering simultaneous measurements of NOx emissions, Flame-Transfer–Function (FTF) and flame imaging.